Strategi Guru dalam Mengatasi Kesulitan Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam di Mts Ummul Quraa Medan Tembung - Fachreza Ibrahim Dalimunthe; Hasnil Aida Nasution; M. Syukri Azwar Lubis (Medan Resource Center, 2022)
The purpose of the study was to determine the planning and implementation of teachers to overcome students' learning difficulties in understanding the subjects of Islamic Cultural History (SKI) at MTs Ummul Quraa Medan Tembung. This type of research is qualitative by using observation and interview guides as instruments. Therefore, the data collection method used observation, interviews, and documentation. The results of the study stated that the teacher determined learning plans to overcome student learning difficulties in SKI subjects by formulating subject objectives, adjusting material, preparing lesson plans and syllabus, adjusting strategies, adjusting methods or media needed, determining assessment and teaching models that facilitate students learn and understand the subject matter. The implementation phase of the learning plan uses learning strategies according to the situation and circumstances (not arbitrary) so that it is carried out effectively and efficiently, using methods that are in accordance with the specified learning strategy, using media that are also in accordance with the specified strategy.